Induced osteoblast differentiation by amide derivatives of stilbene: The possible osteogenic agents. Issue 11 (1st June 2020) - Imran Ahamad, Mohd.; Prakash, Ravi; John, Aijaz A; Wani, Zahoor; Yadav, Deepika; Bawankule, Dnyaneshwar U.; Luqman, Suaib; Khan, Feroz; Singh, Divya; Gupta, Atul
Graphical abstract: Abstract: A series of amide derivatives of stilbene was synthesized and investigated for osteogenic activity. Out of sixteen, seven compounds viz 19c, 19g, 19i, 24b, 25a, 25c and 26a showed significant osteoblast differentiation within 1 pM–1 µM concentrations. Amongst all, 26a was identified as most active molecule which presented effective mineralization of osteoblasts and expression of mRNA of osteogenic marker gene such as BMP-2, ALP, and Runx-2 at 1 pM. In estrogen-deficient balb/c mice, 26a showed significant osteogenic activity at 5 mg-kg −1 body weight dose. The protein expression study for estrogen receptors α and β (ER-α & ER-β) using mouse calvarial osteoblasts (MCOs) and molecular docking analyses showed preferential expression of ER-β by 26a indicating the possibility of ER-β mediated osteogenic activity of 26a .